Pattern of Injuries Observed in Drivers Involved in Fatal Road Traffic Accidents in Tirupati - B. Venkatesulu1 , Vishnu Vardhan Poluru2 , M. Abdul Khalid3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Road Traffic Accidents (RTA) constitute a significant health problem. They constitute the 8th leading cause of death. The aim of this study was to analyse road traffic accidents in Tirupati city and find out the pattern of injuries in drivers who were victims of fatal road traffic accidents. This retrospective study was conducted at the Department of Forensic medicine, S.V Medical College, Tirupati during period 2016 to 2018. Specific findings regarding the injuries sustained to the drivers were noted. A total of 904 people were killed in RTA and were brought to the morgue for postmortem examination. Out of all victims 170 (18.80%) were drivers. Most common age group involved was 30 – 39 yrs. Most of the drivers were males. Polytrauma with lower limb injuries accounted for most common injury in drivers (40.35%) followed by head injury (19.29%) and thoracic injury (12.28%). This study has shown the vulnerability of the vehicle drivers to fatal injuries during RTA. Hence, there is a need for road safety awareness, usage of seat belts, strict enforcement of laws, maintaining vehicle fitness etc. to protect the vulnerable group of people, to decrease the associated morbidity, mortality and reduce the economic burden to the society/ country at large.